STORAGE TIME ON SEED DORMANCY AND GERMINATION IN ETI MUTANTS OF ARABIDOPSIS THALIANA (L) HEYNH - Dasti, Altaf A.; Fatima, Kaniz; Malik, Saeed A. (Journal of Research (Science), 2001)
Previous studies have reported significant influence of maternal environment on dormancy and germination of seeds. We investigated the dormancy level and germinability in seeds obtained from mutants of Arabidopsis thaliana grown under long-day and short-day photoperiodic conditions. Seed dormancy and germination responses were significantly influenced by photoperiod, genotype and storage time. Strong interactions between the main factors imply that the actual pattern of dormancy and germination responses to each factor depends on the levels of other factors. The maternal environment has greater influence on dormancy than that of genotype. However, it appears that there is an overriding effect of storage period in determining levels of dormancy. Duration of the storage period had marked effect on the germination properties of the seeds that are exacerbated by the genetic variation. The  genetic and non-genetic effects disappeared when the seeds were exposed to red light after stratification, implying the transitory nature of maternal influence on seed dormancy and germination characteristics.